Religion and Peace : Global Perspectives and Possibilities - Trauschweizer, Ingo; Sandal, Nukhet A. (Book collections on Project MUSE., 2022)
"If religion can foment conflict, it can also cultivate peace. This perspective underpins the essays in this book, which explore the past, present, and future roles of religion and spirituality in transforming political and social conflicts between and within nations"--